Strategi Dosen Pendidikan Agama Islam dalam Mencegah Ekslusivitas dan Radikalisme Pada Kegiatan Keagamaan Mahasiswa - Abdul Hamid; Amran Mahmud; Aldiawan Aldiawan (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to describe the understanding of the concepts of exclu- sivity and radicalism at the Tadulako University campus, and the strategies that must be carried out by PAI lecturers at Tadulako University specifically at FKIP, through lec- ture material, learning processes, campus activities and lecturer strategies that must be carried out to realize the campus religious, inclusive, moderate, and peace-loving. This type of research is descriptive-qualitative research, data collection methods using field research and qualitative using a survey approach. And types and sources of data, data collection techniques are carried out by: (1) distributing questionnaires to students who are administrators and members of the Darul Ulum. The results of the study show that the attitude of understanding exclusivity and radicalism in the religious activities of the FKIP students at Tadulako University has occurred even though it only reaches 15% to 25% and is categorized as very low.